Total Phenolic, Anticancer and Antioxidant Activity of Ethanol Extract of Piper crocatum Vahl from Pamekasan and Karang Asem - Kristina Mulia; Akhmad Endang Zainal Hasan; Suryani Suryani (Current Biochemistry, 2016)
Cancer is a deadly disease that ranks the second after heart disease. One of the causes of cancer is free radicals causing oxidative stress in humans. Antioxidant is compound that can reduce oxidative stress. The antioxidant activity is closely connected with anticancer activity. It is known that in addition to being an analgesic, aphrodisiac of Java chili also has potential as anticancer. This study examined the potential anticancer and antioxidant from the ethanol extract of Java chili from Pamekasan and Karang Asem. The method used in this study began with the extraction of Java chili using ethanol 70 %, phytochemical testing, determination of total phenol anticancer testing using MTT method on MCF-7 breast cancer cell line and antioxidant testing using DPPH. This study uses Java chili extract derived from Pamekasan and Karang Asem. IC50 value of the cytotoxic activity originating from the area Karang Asem amounted to 63.283 ppm and Pamekasan of 83.662 ppm. IC50 value of antioxidants samples derived from Karang Asem area of 285.613 ppm and are derived from Pamekasan amounted to 288.037 ppm.